-5-3p=-5-6(p-1)

Simple and best practice solution for -5-3p=-5-6(p-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5-3p=-5-6(p-1) equation:


Simplifying
-5 + -3p = -5 + -6(p + -1)

Reorder the terms:
-5 + -3p = -5 + -6(-1 + p)
-5 + -3p = -5 + (-1 * -6 + p * -6)
-5 + -3p = -5 + (6 + -6p)

Combine like terms: -5 + 6 = 1
-5 + -3p = 1 + -6p

Solving
-5 + -3p = 1 + -6p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '6p' to each side of the equation.
-5 + -3p + 6p = 1 + -6p + 6p

Combine like terms: -3p + 6p = 3p
-5 + 3p = 1 + -6p + 6p

Combine like terms: -6p + 6p = 0
-5 + 3p = 1 + 0
-5 + 3p = 1

Add '5' to each side of the equation.
-5 + 5 + 3p = 1 + 5

Combine like terms: -5 + 5 = 0
0 + 3p = 1 + 5
3p = 1 + 5

Combine like terms: 1 + 5 = 6
3p = 6

Divide each side by '3'.
p = 2

Simplifying
p = 2

See similar equations:

| 11/x=4-1/x | | Log(6)(3x)+Log(6)(x-1)=3 | | f(x)=-2x^2+5x+7 | | 5(2x-1)=7x+16 | | 6Log(3x)+6Log(x-1)=3 | | 5X+7=3X+43 | | 25m^2-36n^2=0 | | 2+8(1-9n)=-34 | | 8(6v-5)=v+7 | | x+(2.9)=9.1 | | 8(m-3)=4(4-1) | | x^2+x^3-150=0 | | f(x)=2x^2+5x+7 | | x+(7)=1 | | x/2-6=x/5 | | y=5x^2/3x-2 | | x-(6.1)=3.1 | | 5v-2v=12 | | x+(4.1)=1.9 | | 6(1+8y)=18 | | x+(7.9)=4.1 | | x-(3.1)=4.1 | | 102/50 | | -5n+4n=6 | | x-(7.9)=0.9 | | x+(4.1)=2.9 | | x+(2)=1 | | x-(8.1)=9.9 | | 7(4+8a)=-32 | | x+(5.9)=6.9 | | Q=2.1r+5 | | 2/24=x/30 |

Equations solver categories